FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MEROKOK ELEKTRIK PADA SISWA DI SMA NEGERI 1 TARUMAJAYA KABUPATEN BEKASI TAHUN 2023 - Maulidia, Nanda Afriska; Musniati, Nia (Jurnal Pendidikan Kesehatan (e-Journal), 2024)
E-smoking is a lifestyle among teenagers today. The highest rate of spread of current e-cigarette smoking also occurs in adolescents. Vape is becoming popular as an alternative to smoking. The purpose of this study was to determine The Factors Associated With E-Cigarette Smoking Behavior Among Students of SMA Negeri 1 Tarumajaya, Bekasi Regency in 2023. The study population was SMA Negeri 1 Tarumajaya students with a sample of 109 students. This study used a Cross Sectional study design with Proportional Random Sampling technique. The data used is primary data using a questionnaire in the form of google forms. 109 respondents, 58 respondents (53.2%) had electric smoking behavior and 51 respondents (46.8%) did not have electric smoking behavior. Data analysis using bivariate analysis of chi square test showed a significant relationship between gender (0.000), attitude (0.001) and friends (0.012) with electric smoking behavior. While there is no significant relationship between knowledge (1.000), e-cigarette advertisements in Instagram media (0.274), easy access to e- cigarettes (0.719), pocket money (0.418), family (0.420) and teachers (0.534).